Open innovation as an alternative for strategic development in the aerospace industry in Brazil - Antonio Domingos Padula; Angelo Pássaro; Odair Lelis Gonçalez; Mariana de Freitas Dewes (Journal of Aerospace Technology and Management, 2010)
We present in this paper a case of technological competence development in the aerospace sector in Brazil, by addressing the complete cycle of integrated circuits for satellite applications, an area of high technology which is strategic to the country. The development of technological and business competences is linked to an understanding of the existing relations between different participating institutions, both public and private. There is an effort to establish a network for the development of radiation-hard integrated circuits in Brazil, comprising universities, research centers, private companies, design houses, funding and governmental agencies. These institutions have been working to define their roles, through participation in federally funded projects to develop robust component technology for the aerospace industry in Brazil. As a means to maintain and improve this network, it is suggested that long term planning tools such as technology roadmaps be adopted, as well as measures to increase awareness of and help clarify intellectual property issues, which is considered a significant bottleneck to advance technology development in this area. In this sense, open innovation may be considered an alternative for competitively enhancing the outcomes of the sector.